Undercurrents: The hidden wiring of modern music - Young, Rob (London Continuum, 2002)
For the last twenty years The Wire has fearlessly bypassed fashion in it's search to expose the most innovative, radical, and compelling music from every genre all across the world. As listeners have grown increasingly eclectic and adventurous in their tastes, The Wire has emerged as the most authoritative source on modern music. In Undercurrents some of the best music writers of our time uncover the hidden wiring of the past century's most influential music. Ian Penman discusses how the microphone transformed the human voice and made phantom presences of great singers such as Billie Holiday, Robert Johnson, and Brian Wilson. Christoph Cox demonstrates how the pioneers of live electronic music, the West Coast ensemble Sonic Arts Union, redefined virtuosity for the electronic age. Philip Smith and Peter Shapiro examine Harry Smith's Smithsonian Anthology of American Folk Music, which led to a massive reappraisal of musical values that went far beyond the folk music revival